Evaluación técnica y económica de concentraciones de lactosuero dulce y mucílago de cacao para la obtención de una bebida refrescante - Loor Navia, Mayra Alejandra (2019)
The present work was developed at the Polytechnic Agricultural School of Manabí-Ecuador, with the objective of evaluating technically and economically the concentrations of sweet whey and cocoa mucilage to obtain a refreshing drink. Combinations of two concentrations of whey (55 and 60%) and three percentages of cocoa mucilage (8, 10 and 12%) were made, completing the formulation with water. The trial was conducted with a completely randomized design and three replicas; As an experimental unit, a volume of 250 ml of the beverage was used, which was pasteurized, packaged in plastic containers and stored at refrigeration temperature (4 ° C). Physical-chemical and bromatological analyzes were performed at the time the drinks were obtained. These parameters were processed using the SPSS version 20 program. For sensory analyzes, 40 untrained panelists were required, these results were applied by the Kruskal-Wallis ADEVA. An economic estimate was made for the best treatment (60% whey and 10% cocoa mucilage) cost-benefit of $ 0.22 per liter of the refreshing drink. Concluding that the best treatment is A2 * B2 (60% whey and 10% mucilage).